DEVELOPMENT OF INTERACTIVE LEARNING MEDIA QUIZIZZ LESSON IN NATIONAL MOVEMENT PERIOD MATERIAL TO INCREASE STUDENTS' INTEREST IN LEARNING HISTORY AT SMA NEGERI 9 PEKANBARU - Bevi Anjelia Lestari; Rhoma Dwi Aria Yuliantri (SOSIOEDUKASI, 2026)
This study aims to develop interactive learning media using Quizizz Lesson on the National Movement Era material and test its validity, practicality, and effectiveness in enhancing students' interest in learning history. The research uses the ADDIE model (Analysis, Design, Development, Implementation, Evaluation) with subjects from class XI of SMA Negeri 9 Pekanbaru, consisting of 30 experimental and 30 control group students. The instruments used are interest questionnaires, expert validation sheets, and student practicality test sheets. The validity results show an average value of 0.95 (Highly Valid), practicality at 92.89% (Highly Practical), and effectiveness with an N-Gain of 0.52 (Medium) and a significant difference between the experimental and control groups (p < 0.05). The Quizizz Lesson media proves to be feasible, practical, and effective in enhancing students' interest in learning the National Movement Era material